2018
DOI: 10.31107/2075-1990-2018-5-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effect of Population Ageing and Pension Reforms

Abstract: The paper considers impact of population ageing on the economic growth and sustainability of pension systems. The analysis demonstrates that ageing has negative effect on the labor force and labor productivity, and thus results in a slowdown of economic growth and an increase of public spending. The most effective policy option is to raise the retirement age, while an increase in contribution rates or other taxes is the worst reaction. This recommendation is relevant for any countries at different stages of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Большая часть данных программ основана на принципах фондирования. Однако в некоторых странах (Франция, Германия, Япония) в основе корпоративных пенсионных программ лежат распределительные принципы 3 [14,[17][18][19][20].…”
Section: методология и материалы исследованияunclassified
See 2 more Smart Citations
“…Большая часть данных программ основана на принципах фондирования. Однако в некоторых странах (Франция, Германия, Япония) в основе корпоративных пенсионных программ лежат распределительные принципы 3 [14,[17][18][19][20].…”
Section: методология и материалы исследованияunclassified
“…Несмотря на популярность исследований накопительных элементов пенсионной системы среди отечественных и зарубежных экономистов в последние четыре года (см. : Е. Тарандо, Ц. Ван (2019) [1], Е. Гурвич (2019, 2018) [2,3], М. А. Иванова (2018) [3], И. Мадеро-Кабиб и др. (2019) [4], И. М. Реутова…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In high-income countries, the share of elderly people increased between 1950 and 2015 from 8% to 17%, in Russia from 5% to 13%, and by 2050 it will reach 27% in developed countries and 22% in our country. In general, from 1950 to 2050, the share of the elderly population in the world will increase by 3.1 times, in developed countries -by 3.4 times and in Russia -by 4.6 times [2]. A number of recent studies have not found a relationship between labor productivity and age [3].…”
Section: Introductionmentioning
confidence: 99%
“…R&D and innovations are the key components of this strategy, while increasing productivity and creating new jobs are catalysts for more innovative products and services. Since innovations serve as the basis for sustainable growth and competitiveness of the economy in the modern world, there exists high popularity of supportive measures for innovations (Gurvich & Ivanova, 2018).…”
Section: Introductionmentioning
confidence: 99%